2014
DOI: 10.1001/jamainternmed.2013.12844
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Grafting vs Percutaneous Coronary Intervention and Long-term Mortality and Morbidity in Multivessel Disease

Abstract: IMPORTANCE Recent trials of percutaneous coronary intervention (PCI) vs coronary artery bypass grafting (CABG) for multivessel disease were not designed to detect a difference in mortality and therefore were underpowered for this outcome. Consequently, the comparative effects of these 2 revascularization methods on long-term mortality are still unclear. In the absence of solid evidence for mortality difference, PCI is oftentimes preferred over CABG in these patients, given its less invasive nature. OBJECTIVES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
141
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(169 citation statements)
references
References 29 publications
13
141
1
11
Order By: Relevance
“…This data differs from the data in the literature, where outpatients are commonly stratified in class II and III, and FC I patients rarely have any health monitoring for the slight and sporadic symptoms of the heart disease ( ALMEIDA et al, 2013;SIPAHI et al, 2014).…”
Section: Discussioncontrasting
confidence: 97%
“…This data differs from the data in the literature, where outpatients are commonly stratified in class II and III, and FC I patients rarely have any health monitoring for the slight and sporadic symptoms of the heart disease ( ALMEIDA et al, 2013;SIPAHI et al, 2014).…”
Section: Discussioncontrasting
confidence: 97%
“…However, this extraordinary reduction should be viewed in wider perspective; indeed, although not directly the objective of the current investigation, “no‐touch” OPCAB might offer the long‐term survival benefit of CABG over PCI,2, 35 together with similar or lower than PCI 30‐day stroke rates 36, 37. The discussion about potential shortcomings of CABG as compared to PCI was fueled after the first large industry‐funded trial3 found significantly higher rates of major adverse cardiac and cerebrovascular events in the PCI group (17.8% versus 12.4% for CABG; P =0.002), in large part because of an increased rate of repeat revascularization (13.5% versus 5.9%); however, at 12 months, strokes were 4‐fold more likely to occur with CABG (2.2% versus 0.6% with PCI; P =0.003).…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, patients with cardiovascular disease may incorrectly self‐report smoking status since they are under the pressure to quit smoking 38. For CABG, several trials have shown its survival benefits compared with percutaneous revascularization or medical treatments in patients with severe coronary heart disease 39, 40, 41. Thus, the prognostic value of CABG may depend on patient characteristics.…”
Section: Discussionmentioning
confidence: 99%